Telaah Kesalahan Penggunaan Kalimat Efektif pada Karangan Eksposisi Siswa Kelas V SDN Kebon Dalem - Pratiwi, Oka Endah; Sundari, Nenden; Suzanti, Lizza (Didaktika, 2021)
The skill of writing expository essays can be used as a medium to improve the use of good and appropriate language for elementary school students. This study describes errors in using effective sentences in exposition essays in the fifth grade of Kebon Dalem State Elementary School, which consists of using effective sentence structures, Subject-Verb-Object-Adverb form (SPOK) conjunctions, and punctuation marks. This study used a qualitative approach with a qualitative descriptive method. The subject of this research is the fifth grade of Kebon Dalem State Elementary School, with as many as seventeen students. The research instrument was used in the form of interviews and written documents in student expositions essays. The results showed that the student’s exposition essay writing was good because it was seen from the mistakes that students did not make. Disposition errors in the use of effective sentence as a whole: there are five higher errors in effective sentence structures, including SPOK, three higher errors in the use of conjunctions, and five higher errors in punctuation marks. The errors were assessed slightly because each student wrote three paragraphs and ten to twelve sentences. It shows that the types of mistakes in using effective sentences made by students in expository essays are still very diverse.